EFFECT OF MUḌĀRABAH SAVINGS PROFIT SHARING AND MUḌĀRABAH DEPOSITS ON NET PROFIT IN PT. BANK SYARIAH MANDIRI, Tbk IN 2011-2018 - indah pratiwi; azwar hamid; veri pramudia (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Based on data obtained at PT. Bank Syariah Mandiri Tbk, there is a phenomenon that is not in accordance with the theory, Muḍārabah savings in the second quarter of 2013 decreased but net income increased. In 2015-2016 muḍārabah deposits decreased but net income increased. So the formulation of this study is whether the profit sharing of muḍārabah savings and muḍārabah deposits has a partial and simultaneous effect on net income at PT. Bank Syariah Mandiri, Tbk Year 2011-2018. The aim of the study is to determine the effect of muḍārabah savings and muḍārabah savings partially and simultaneously has an effect on net income at PT. Bank Syariah Mandiri, Tbk Year 2011-2018. This research is a quantitative study with secondary data and sampling techniques using purposive sampling of as many as 32 samples. Data analysis methods used in this research are descriptive tests, normality tests, heteroscedasticity tests, multicollinearity tests, auto operation tests, multiple regression tests, coefficient of determination tests (R2), partial tests (t-test), and simultaneous tests (F). The results of this study indicate that the R Square value of 19 percent while the remaining 81 percent (100-19) is influenced by other variables not examined in this study.